Approximation of the function with spline discrete bases - Білецький, А. Я.; Шелевицький, І. В.; Шутко, В. М. (Proceedings of National Aviation University (archive), 1999)
Considered is approximation of discrete data given by means of local splines. The particularity of approximation is in syntheses of discrete spline bases with pulse-frequency features or energy spectrums, which are coordinated with data. The problem is reduced to finding the necessary pu1scJ features of nonrecursive numeric filters. Displaced in time local functions form qua«°icftogonal spline base. The typical particularities of such base allow effectively to realize the calculation of generalised factors Fourier in received bases